Two Parabolic Equations with Hysteresis (Journal of Partial Differential Equations, 2020)
In this paper we discuss the properties of hysteresis phenomena and give some conclusions about two parabolic equations with hysteresis raised by A. Visintin.
Keywords: Hysteresis operator; Leray-Schauder fixed point theorem; periodic solution; parabolic equation